Insert Discs

Calculus Level 2

Show that

e x e 2 x + 1 d x ∫\frac{e^x}{e^{2x}+1} dx = arctan ( e x ) \arctan (e^x) + C C ,

where C C is a constant of integration.


The volume of the solid formed by revolving the curve

f ( x ) f(x) = e x e 2 x + 1 \sqrt{\frac{e^x}{e^{2x}+1}}

bounded between x = l n 3 ln 3 x = ln\sqrt{3} - \ln{3} and x = 1 2 ln 3 x = \frac{1}{2}\ln{3} around the x x axis can be expressed as π 2 a \frac{\pi ^2}{a} . Find the value of a a .

Learn more


The answer is 6.

This section requires Javascript.
You are seeing this because something didn't load right. We suggest you, (a) try refreshing the page, (b) enabling javascript if it is disabled on your browser and, finally, (c) loading the non-javascript version of this page . We're sorry about the hassle.

2 solutions

Volume of Revolution \textrm{Volume of Revolution} , V = ζ Γ π ( f ( x ) ) 2 d x V=\int_ζ^{Γ} π (f(x))^2 dx = 1 2 l o g ( 3 ) 1 2 l o g ( 3 ) π e x e 2 x + 1 d x =\int_{\frac{-1}{2}log(3)}^{\frac{1}{2}log(3)} π \frac{e^x}{e^{2x} +1}dx take e x = t e^x =t and the integral becomes 1 / 3 3 π d t t 2 + 1 \int_{1/√3}^{√3} π\frac{dt}{t^2 +1} = π [ t a n 1 t ] 1 / 3 3 =π [tan^{-1} t ]^{√3}_{1/√3} = π ( π 3 π 6 ) =π (\frac{π}{3} - \frac{π}{6}) = π 2 6 =\frac{π^2}{6}
EDIT🍎 \textrm{EDIT🍎} π 2 6 = 1 1 2 + 1 1 2 + 1 3 2 + 1 4 2 + \frac{π^2}{6} = \frac{1}{1^2} + \frac{1}{1^2} + \frac{1}{3^2} +\frac{1}{4^2} + \cdots

Ethan Mandelez
Dec 2, 2020

0 pending reports

×

Problem Loading...

Note Loading...

Set Loading...